2020
DOI: 10.1080/16549716.2020.1776507
|View full text |Cite
|
Sign up to set email alerts
|

National incidence, prevalence and disability-adjusted life years (DALYs) of common micronutrient deficiencies in Ethiopia from 1990 to 2017: estimates from the global burden of diseases study

Abstract: Background: Understanding the national burden and trend of micronutrient deficiencies helps to guide effective intervention strategies under various circumstances. There is, however, a lack of evidence on trends, age-and sex-specific variations in Ethiopia. Objective: This study aimed to provide evidence on the trends of common micronutrient deficiencies including, dietary iron, iodine, vitamin A and other nutritional deficiencies in Ethiopia, from 1990 to 2017, using findings from the Global Burden of Disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…27 In addition, iodine deficiency in women can lead to devastating effects during pregnancy, leading to miscarriage, stillbirth, congenital malformations, neurosis, and increased perinatal and infant mortality. 26 We also found that the burden of iodine deficiency increased with higher SDI and HAQ index among developed countries. Most governments of developed countries, however, still give low priority to addressing iodine deficiency in their populations.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…27 In addition, iodine deficiency in women can lead to devastating effects during pregnancy, leading to miscarriage, stillbirth, congenital malformations, neurosis, and increased perinatal and infant mortality. 26 We also found that the burden of iodine deficiency increased with higher SDI and HAQ index among developed countries. Most governments of developed countries, however, still give low priority to addressing iodine deficiency in their populations.…”
Section: Discussionsupporting
confidence: 52%
“…The high prevalence in sub-Saharan Africa could be due to an interaction among inadequate dietary diversity, poor sanitation and infectious diseases. 26 As the most populous country in South Asia, India reported that household iodized salt consumption was only 51%, indicating that iodine intake is insufficient at the population level. 27 However, this situation is not limited to underdeveloped countries.…”
Section: Discussionmentioning
confidence: 99%
“…To our best knowledge, there are only a limited number of analyses on VAD burden in specific populations and limited regions based on the previous Global Burden of Disease (GBD) study [ 12 , 13 ]. Moreover, the previous GBD analyses have focused more on loss of vision due to VAD rather than VAD itself [ 2 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…3-155.4]. 14 In nearly all countries where iodine deficiency occurs, it is now well recognized that the most effective way to achieve the virtual elimination of IDD is through universal salt iodization (USI). It is recommended as the most cost-effective, safe, and sustainable way to eliminate IDD.…”
Section: Introductionmentioning
confidence: 99%
“…13 In 2017, the total Disability Adjusted Life Years due to dietary iodine deficiency was estimated to be 89 600 [95% uncertainty interval 48.3–155.4]. 14 In nearly all countries where iodine deficiency occurs, it is now well recognized that the most effective way to achieve the virtual elimination of IDD is through universal salt iodization (USI). It is recommended as the most cost-effective, safe, and sustainable way to eliminate IDD.…”
Section: Introductionmentioning
confidence: 99%